Sufistic Consciousness as A Foundation of Religious Well-Being in Ibn ‘Arabi’s Teaching to Understanding Existential Uncertainty - Putra, Andri Azis; Kuswanjono, Arqom; Munir, Misnal (Jurnal Theologia, 2021)
Consciousness is one of the most vital states of human existence. One of its roles is to explain the context of life in the uncertainty of life itself. The most influential aspect of this means is the human fundamental religious state. This paper aimed to find clarity of humans’ consciousness and religious well-being relation and to obtain an existential ground for a progressive scheme for both subjects as well. This research will use a philosophical-hermeneutic approach with existential uncertainty as to its material object and Sufistic consciousness as the formal object. This research showed that human religious well-being can be used as Sufistic consciousness ground to adjust human existential dilemma. The scheme used is to determine the position of each divine theophany (tajalliy) element on its impact on the level of human psychological consciousness. Al-a'yan ats-tsabitah has taken a leading role in this research, especially in explaining the impossible and possible things for the human condition.